1996
DOI: 10.1159/000282918
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ischemia after ESWL: Detection of Free Oxygen Radical Scavenger Enzymes in Renal Parenchyma Subjected to High-Energy Shock Waves

Abstract: To evaluate the degree of ischemic formation at the tissue level after high-energy shock wave (HESW) application in a time- and dose-dependent manner, an experimental study in rabbits was performed. Following varying numbers of HESWs (1,000–2,000–3,000 shock waves) under fluoroscopic localization, treated kidneys were removed, by assessing tissue concentrations of two different free-radical scavenger enzymes (superoxide dismutase and catalase) the degree of formation of free oxygen radicals (i.e. ischemia) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 8 publications
(12 reference statements)
1
27
0
Order By: Relevance
“…Evidence has indicated previously (44) that the biological effect of ESW treatment may be mediated by bubble cavitation or acoustic energy. The ESW-induced acoustic energy could also elicit oxygen free radicals (45). However, the oxidative stress from the ESW treatment has been previously implicated in tissue damage (42 It has been shown that O 2 Ϫ can act as an important signal for the mitogenesis of certain cells (47) and induce cardiac fibroblast proliferation associated with an increase in TGF-␤1 expression (48).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has indicated previously (44) that the biological effect of ESW treatment may be mediated by bubble cavitation or acoustic energy. The ESW-induced acoustic energy could also elicit oxygen free radicals (45). However, the oxidative stress from the ESW treatment has been previously implicated in tissue damage (42 It has been shown that O 2 Ϫ can act as an important signal for the mitogenesis of certain cells (47) and induce cardiac fibroblast proliferation associated with an increase in TGF-␤1 expression (48).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and experimental studies have demonstrated that oxygen free radicals, which are toxic partial reduction products of oxygen, have a vital role in the development of renal parenchymal damage during ischemia [13, 14, 15]. In the case of transient ischemia and subsequent reperfusion, tightly controlled oxygen metabolism will be disrupted, resulting in an excess production of reactive oxygen species [14, 15, 16]. Tissues contain enzymatic and nonenzymatic defense mechanisms, known antioxidant defense potential (AOP) to protect themselves against free radical damages occurring during metabolic events.…”
Section: Introductionmentioning
confidence: 99%
“…Even so, findings by these and other investigators of such phenomena as intraparenchymal hemorrhage, reduced renal blood flow, and urinary excretion of enzymatic markers of cellular injury naturally led to speculation that ischemia and subsequent tissue injury had occurred. In addition, other researchers proposed that oxidative stress associated with ischemia induced by SWL may also contribute to the resulting tissue injury (Sarica et al, 1996a;Cohen et al, 1998;Brown et al, 2000;Munver et al, 2002). Support for a possible role of oxidative stress in the tubular injury caused by shock waves comes from several studies in which inhibitors of oxidative stress reduced the urinary excretion of enzymatic markers of tubular injury (Strohmaier et al, 1991(Strohmaier et al, , 1993(Strohmaier et al, , 1994a(Strohmaier et al, , b, 1999(Strohmaier et al, , 2002Benyi et al, 1995;Ogiste et al, 2003) or diminished the histological signs of tissue injury (Fegan et al, 1991;Yaman et al, 1996;Sarica et al, 1997;Biri et al, 1998) after SWL.…”
Section: Discussionmentioning
confidence: 99%